2017
DOI: 10.1177/2055217317715485
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and discontinuation of dimethyl fumarate and fingolimod in clinical practice at 24-month follow-up

Abstract: BackgroundDimethyl fumarate and fingolimod are oral disease-modifying therapies approved to treat relapsing multiple sclerosis. Prior observational studies and our previous 12-month investigation showed comparable clinical efficacy.ObjectiveThe purpose of this study was to assess real-world efficacy and discontinuation of dimethyl fumarate and fingolimod over 24 months in patients with multiple sclerosis.MethodsPatients treated with dimethyl fumarate (n = 395) or fingolimod (n = 264) completed 24-month follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 28 publications
4
51
2
Order By: Relevance
“…A single-centre propensity score-weighted study among 659 patients did not find a statistically significant difference in the rate of relapses between patients treated with fingolimod or dimethyl fumarate over 2 years. In that study, 0.20–0.21 on-treatment relapses per patient and year were reported, but the mean time to the first relapse was markedly longer in fingolimod (7.56 months) than dimethyl fumarate (3.83 months) 10. A network meta-analysis of two pooled post hoc analyses of placebo-controlled trials reported non-significant trends favouring fingolimod over dimethyl fumarate in relapse frequency and 3-month confirmed disability progression in highly active MS 7…”
Section: Discussionmentioning
confidence: 85%
“…A single-centre propensity score-weighted study among 659 patients did not find a statistically significant difference in the rate of relapses between patients treated with fingolimod or dimethyl fumarate over 2 years. In that study, 0.20–0.21 on-treatment relapses per patient and year were reported, but the mean time to the first relapse was markedly longer in fingolimod (7.56 months) than dimethyl fumarate (3.83 months) 10. A network meta-analysis of two pooled post hoc analyses of placebo-controlled trials reported non-significant trends favouring fingolimod over dimethyl fumarate in relapse frequency and 3-month confirmed disability progression in highly active MS 7…”
Section: Discussionmentioning
confidence: 85%
“…[10][11][12] There were no substantial differences regarding the 12 and 24 months analyses. In comparison with two studies with an observation period of 24 months and another study with an observation period of 12 months, we found similar relapse rates.…”
Section: Re Sultsmentioning
confidence: 80%
“…4 No difference in ARR between teriflunomide and IFNβ-1a was seen in TENERE. [9][10][11][12][13][14][15] These discrepancies ask for further investigations to confirm or rebut the published findings. [9][10][11][12][13][14][15] These discrepancies ask for further investigations to confirm or rebut the published findings.…”
mentioning
confidence: 91%
“…Dimethyl fumarate has been compared with a number of alternative treatments using CE research methods, including claims-based analyses [7, 8], a cross-sectional study [9], and a number of PSM analyses based on registries [10–14]. In the PSM analyses performed to date, DMF showed improved clinical effectiveness in terms of reductions in ARR and time to first relapse (TTFR) events versus IFN, GA, and TERI [13, 14], and a similar rate of relapse as FTY [10–12, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In the PSM analyses performed to date, DMF showed improved clinical effectiveness in terms of reductions in ARR and time to first relapse (TTFR) events versus IFN, GA, and TERI [13, 14], and a similar rate of relapse as FTY [10–12, 14]. To support this growing body of real-world evidence, this CE analysis based on the German NeuroTransData (NTD) multiple sclerosis (MS) registry was conducted to assess real-world CE of DMF compared with IFN, GA, TERI, and FTY in PSM cohorts of patients with RRMS.…”
Section: Introductionmentioning
confidence: 99%